(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
The poem Vozes-Mulheres, by Conceição Evaristo (2008), refers to different historical periods according to ancestral experiences. Woman, black and lived in the favela, the author leads us to reflect on racism, sexism and classism in Brazil. This is also the objective of this essay, which, by dialoguing with the poem, analyzes how these structures reverberate until today in the country’s social practices.